PREGNANCY EXERCISE IMPACT TO PERINEAL TEAR IN NORMAL LABOR - Ayunda Ardiana; Budi Utomo; K. Kasiati; Bambang Purwanto (Universitas Airlangga, 2021)
Abstract   Background: Perineal tear is the tearing of the pelvic floor muscles. Based on the literature review and previous research, perineal tear often occur in labor, especially in primigravida. Pregnancy exercise is a physical activity that carried out by pregnant women. This study aims to determine the relationship between pregnancy exercise and perineal tear in normal labor at the Pratama Anugrah Clinic in Surabaya. Methods: This study uses an observational analytic method with a retrospective time approach. The number of samples was 34 case groups (perineal tears) and 34 control groups (no perineal tears) in normal delivery using purposive sampling. The instruments used are medical records, written interviews, cameras and checklists. Data analysis used chi square statistical test with a significance level of 0.05. Results: The results showed that there were still many mothers who did not do pregnancy exercise during their pregnancy as many as 43 (63.2%). Mothers who did not practice pregnancy exercise experienced more perineal tears as much as 27 (79.4%), while mothers who did practice pregnancy exercise experience perineal tear in normal labor that is 18 (53%). Result of chi square statistical tests obtained p value 0.006 (p<0.05). Conclusion: Pregnancy exercise minimizes perineal tear in normal delivery.